Pertumbuhan Dan Produksi Sawi (Brassica juncea L) Pada Inceptisol Dengan Aplikasi Kompos Tandan Kosong Kelapa sawit - Taufik Hidayat; Wardati '; Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research is to know the effect of compost of oil palm bunches and determine the best dose for the growth of the mustard plant on Inceptisol. This reseacrch was conducted at The Agricultural Experiment Station ofFaculty agriculture, University of Riau, on February to April 2013. The research used a Completely Randomized Design (CRD) which consisted of 5 treatments, including 0. 0,5, 1, 1,5, and 2 kg of compost of oil palm bunches and 6 replications. The observation parameters in this research are including plant height, number of leaves, leaf area, root volume, fresh weight of plant consumption, and the analysis of chemical properties of soil as supporting data consists of a C-organic, CEC, pH and N-total. The results showed that the application of compost in some doses show the real difference on all the parameters, namely plant height, leaf number, leaf area, root volume and fresh weight of plant consumption. The application of compost with a dose of 1,5 kg/plot to 2 kg/plot shows the growth and production of the best. Keywords : Inceptisol, Mustard, Compost, Oil Palm Bunches